Cluster-adjusted DEA efficiency in the presence of heterogeneity: An application to banking sector - Kekoura Sakouvogui; Saleem Shaik; Kwame Asiam Addey (Open Economics, 2020)
This paper improves on the issues of extreme data points and heterogeneity found in the linear programming data envelopment analysis (DEA) by presenting a cluster-adjusted DEA model (DEA with cluster approach). This analysis, based on efficiency, determines the number of clusters via Gap statistic and Elbow methods. We use the December quarterly panel data consisting of 122 U.S agricultural banks across 37 states from 2000 to 2017 to estimate the cluster-adjusted DEA model. Empirical results show differences in the estimated DEA efficiency measures with and without a clustering approach. Furthermore, using non-parametric tests, the results of Ansari-Bradley, Kruskal Wallis, and Wilcoxon Rank Sum tests suggest that the cluster-adjusted DEA model provides statistically better efficiency measures in comparison to the DEA model without a clustering approach.
Keywords: A10; C10; C14; C44; G21; 330; Banking; Cluster analysis; Efficiency Analysis; Nonparametric tests